Pengaruh Struktur Modal, Profitabilitas, dan Ukuran Perusahaan Terhadap Keputusan Investasi dengan Kebijakan Deviden sebagai Variabel Intervening (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of capital structure, profitability, and company size on investment decisions of Islamic companies listed on the Jakarta Islamic Index, with dividend policy as an intervening variable. The study uses a quantitative approach with secondary data in the form of annual financial reports of companies for the period 2022–2025. The research sample was determined using a purposive sampling technique based on certain criteria. Data analysis was conducted through panel data regression supported by classical assumption testing, partial and simultaneous hypothesis testing, coefficient of determination, and the Sobel Test to examine the mediating role of dividend policy. The results show that capital structure has no significant effect on dividend policy or investment decisions. Profitability has a significant effect on dividend policy and investment decisions, while company size has a significant effect on dividend policy but not on investment decisions. Furthermore, dividend policy has a positive and significant effect on investment decisions. The Sobel Test results indicate that dividend policy is only able to mediate the effect of profitability on investment decisions. These findings confirm that profitability and dividend policy are important factors in explaining investment decisions of Islamic companies. Therefore, management needs to maintain earnings quality and dividend policy consistency to increase investor confidence.